Infectivity and pathogenicity of Cryptosporidium andersoni to a novel host, southern multimammate mouse (Mastomys coucha) - Ondráčková, Zuzana (Jihočeská univerzita, 2009)
The infectivity and pathogenicity of Cryptosporidium andersoni (bovine isolate) for neonatal and adult southern multimammate mice (Mastomys coucha) was studied using transmission experiments. Mastomys coucha seems to be a useful laboratory model for study of C. andersoni infection.
Keywords: Cryptosporidium andersoni; Mastomys coucha; Infectivity; Pathogenicity; 18S rRNA gene